The Interactive Role of Wind and Water in Functioning of Drylands: What Does the Future Hold?. (3rd September 2018) - Okin, Gregory S; Sala, Osvaldo E; Vivoni, Enrique R; Zhang, Junzhe; Bhattachan, Abinash
Abstract: Feedback mechanisms between abiotic and biotic processes in dryland ecosystems lead to a strong sensitivity to interannual variations in climate. Under a future regime of higher temperatures but potentially increased rainfall variability, drylands are anticipated to experience changes in wind and water transport that will alter plant community composition and feedback on landscape connectivity. Here, we present a conceptual framework for understanding the coupling of vegetation productivity, aeolian transport, and hydrologic connectivity under anticipated changes in future climate, which suggests that a more extreme climatic regime will lead to more connected landscapes with attendant losses in soil, nutrient, and water resources. When enhanced connectivity triggers state changes, irreversible changes in ecosystem functioning can occur, with implications for the future of global drylands.